Answer:
b., (2, 5, 3).
Explanation:
x- y + z = 0
-5x + 3y - 2z = -1
2x - y + 4z = 11
Multiply the first equation by 2
2x - 2y + 2z = 0
Adding this to the second equation we get
-3x + y = -1 ........... (A)
Multiplying the second equation by 2 and adding to the third equation we get:
-8x + 5y = 9................(B)
Multiplying equation (A) by -5 and adding to equation (B) we get:
7x = 14
x = 2.
Substituting -3(2) + y = -1 so y = -1 + 6 = 5.
And substituting in the first equation fo x and y:
2 - 5 + z = 0
z = 5-2 = 3.